Novel BDNF-regulatory microRNAs in neurodegenerative disorders pathogenesis: An in silico study. (December 2019) - Khani-Habibabadi, Fatemeh; Askari, Shahrzad; Zahiri, Javad; Javan, Mohammad; Behmanesh, Mehrdad
Graphical abstract: Highlights: Differential expression of BDNF-regulating miRNAs in neurodegenerative disorders. Regulation of BDNF-related pathways by candidate miRNAs. Regulation of transcription factors binding BDNF promoter by candidate miRNAs. Sponging candidate miRNAs by BDNF-correlated long noncoding RNAs. Diverse correlation scores among candidate miRNAs and BDNF, based on the conditions. Abstract: Brain-derived neurotrophic factor ( BDNF ) is a neurotrophic factor with various roles in the central nervous system neurogenesis, neuroprotection, and axonal guide. By attaching to Tropomyosin receptor kinase B (TrkB) receptor, this protein triggers downstream signaling pathways which lead to cellular growth, proliferation, survival, and neuroplasticity. Deregulation at mRNA level is involved in various central nervous system disorders including, Huntington, Alzheimer's, Multiple Sclerosis, and Amyotrophic Lateral Sclerosis diseases. Considering the importance of BDNF functions, deciphering the regulatory mechanisms controlling BDNF expression level could pave the way to develop more accurate and efficient treatments for neurological diseases. Among different regulatory systems, microRNAs (miRNAs) play prominent roles by targeting genes 3′ untranslated regions. In this study, 127 validated and bioinformatic-predicted miRNAs with potentially regulatory roles in BDNF expression were analyzed. Various aspects of miRNAsö possible functions were assessed by bioinformatic online tools to find their potential regulatory functions in signaling pathways, neurological disorders, expression of transcription factors and miRNAs sponge. Analyzed data led to introduce 5 newly reported miRNAs that could regulate BDNF expression level. Finally, high throughput sequencing data from different brain regions and neurological disorders were analyzed to measure correlation of candidate miRNAs with BDNF level in experimental studies. In this study, a list of novel miRNAs with possible regulatory roles in BDNF expression level involving in different neurological disorders was introduced.